Inequality and the New Deal - Christian A. Belabed (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2016)
There is a large body of literature analyzing the onset of the Great Depression or the factors influencing economic recovery in the 1930s, especially the New Deal. The role of income inequality before and during the Great Depression, however, has almost never been discussed thoroughly. This paper attempts to answer two questions. Firstly, was inequality perceived as a problem by the Roosevelt administration? Secondly, did the New Deal incorporate these concerns such that economic policy design did take seriously the problem of inequality? Using official documents such as transcripts of Roosevelt's inaugural speeches, fireside chats and press conferences, this paper finds that top-end inequality was not recognized as a major political topic. Restoring the purchasing power of workers and farmers, however, appears to have been a political goal of the administration. The impact of New Deal policies on top-end income inequality or the wage share, however, can only be considered as modest. Only World War II and the long-term legislation of the New Deal may be considered successful in reducing top income and wealth shares and raising the wage share. – – Ein großer Teil der akademischen Literatur beschäftigt sich entweder mit den Ursachen der Großen Depression oder der wirtschaftlichen Erholung in den 1930er Jahren und den Faktoren die sie beeinflussten. Die Rolle der Einkommens- und Vermögensverteilung im Kontext der Großen Depression wurde allerdings sehr selten umfassend untersucht. Dieses Papier soll zwei Fragen beantworten. Erstens, wurde Ungleichheit von der Roosevelt-Administration als Problem wahrgenommen? Zweitens, spielte Ungleichheit beim Design der Wirtschaftspolitik (New Deal) in den 1930er Jahren eine Rolle? Die Resultate zeigen, dass Topeinkommens- und Topvermögensungleichheit, also die personelle Einkommensverteilung, kein bedeutendes politisches Thema waren. Die Wiederherstellung der Kaufkraft unterschiedlicher Gesellschaftsgruppen, wie Arbeiter oder Landwirte, scheint allerdings ein wichtiges Anliegen der Regierung gewesen zu sein. Der Einfluss des New Deal auf die Einkommens- und Vermögensverteilung am oberen Ende der Verteilung war dementsprechend moderat. Der Eintritt der USA in den Zweiten Weltkrieg, in Verbindung mit den langfristigen Reformen des New Deal könnten jedoch Auswirkungen sowohl auf die Topeinkommens- und Topvermögensanteile, als auch auf die Lohnquote gehabt haben.
urn:nbn:de:101:1-20160613760
Keywords: D31; D33; E02; E21; E25; G01; N12; N22; N32; N62; 330; inequality; income and wealth distribution; new deal; Roosevelt; Great Depression